The characteristics of serum lipid spectrum in PanNENs and its correlation with clinicopathological features and prognosis - Meng, Yu-Fan; Fan, Zhi-Yao; Yang, Jian; Li, Yong-Zheng; Liu, Shu-Jie; Gao, Chang-Hao; Gao, Xin; Pang, Chao-Yu; Zhan, Han-Xiang (Frontiers in Endocrinology, 2023)
Background: The role of dyslipidemia in pancreatic neuroendocrine tumors (PanNENs) is unclear. The aim of this study is to analyze the characteristics of serum lipid spectrum in PanNENs, and the effect of the variation in lipid profile on the development of PanNENs clinicopathological features and prognosis. Methods: All PanNENs patients between November 2012 and September 2020 in the authors' research center were identified from patient medical records and databases. A total of 185 with PanNENs patients were ultimately included in this study, including 100 nonfunctional PanNENs and 85 insulinomas. Clinicopathologic features, serum lipid level and overall survival results were retrospectively analyzed using statistical methods. Results: This retrospective cohort study displays that insulinoma patients exhibit increased serum HDL level compared to non-functional PanNENs (OR:2.522; 95% CI:1.096-5.803; P = 0.030). High levels of HDL were negatively correlated with tumor diameter (OR 0.233; 95% CI: 0.069-0.790; P=0.019). However, there was no significant difference between PanNENs patients with hyperlipidemia and normal blood lipid level in tumor location, tumor diameter, pathological grade, and clinical stage. In the univariate and multivariate analyses, there is also no significant correlation between hyperlipidemia and overall survival. Conclusions: HDL was negatively correlated with the tumor size of PanNENs. The serum HDL level of insulinoma patients is higher than nonfunctional PanNENs.